Modeling the Linguistic Topology of Translation Process: General Principles - Anna I. Krivoruchko; Sinxiun Kan (Виртуальная коммуникация и социальные сети)
Cognitive research in translation is currently at its peak. The authors studied L. V. Kushnina’s synergetic concept of translation space in an interaction with the topological fields of translation to develop a linguistic topological model of translation as a process. The analysis yielded graphic constructs represented by topologically structured spaces that illustrate the process of interlingual and intercultural interaction. The research relied on P. A. Florensky’s idea of the language of spatial objects and the provisions of philological and translation topology developed by L. V. Polubichenko, who studied the variant vs. invariant patterns of different philological objects, from words to texts. The current Chinese translation studies show similar ideas (see: Wu Dan, Ding Xiuhei, Zhao Genglin, Jiang Shengnan, etc.). The article visualizes the modern translation paradigm from the perspective of linguistic topology. Translation is a multifunctional verbal and mental activity that unites various objects in the spaces between the sender, the translator, and the recipient. The resulting topological translation model represents the linguistic topology of interlingual communication at the intersection of cognitive topology, linguistics, translation theory and practice, and cognitive translation studies.